Pengaruh PDB, Kurs Dollar AS, IHPB, dan PMA Terhadap Impor Barang Modal di Indonesia - Apsari Anandari, I Gusti Agung Ayu; Yogi Swara, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 3, Maret 2015 (pp. 139 - 219), 2015)
Trade openness is a forthcoming challenge for Indonesia. There will be advantages regarding to access in goods but it also heating up the market competitiveness. In regards to facing the market competitiveness, Indonesia has to face the ugly truth that the demands of important thing needed to increase productivity, which is capital goods, are fulfilled by imports from other countries. This study examines the impact of GDP, exchange rate, wholesale price index, and FDI on capital goods import in Indonesia. Time series data is used within 20 years period of time, from 1994 to 2013. Regression analysis is carried out using SPSS.  After the analysis is out it is revealed that all four independent variables simultaneously affect the dependent one in significant way while partially, GDP, wholesale price index, and FDI has positive and significant impact on capital goods import. On the other hand, exchange rate has negative and significant impact on capital goods import. Analysis of the standardized coefficient beta values revealed that among four independent variables tested, FDI has the largest effect on capital goods import of Indonesia.
Keywords: Impor barang modal, PDB, kurs, IHPB, PMA